Pelatihan Kader Posyandu Balita di Korong Sungai Jilatang, Kabupaten Padang Pariaman - Sri Oktarina; Agustika Antoni (Warta Pengabdian Andalas, 2020)
Posyandu is one form of Community Based Health Efforts (UKBM) managed from, by, for and with communities, to empower and provide convenience to the public in obtaining basic health services. Korong Sungai Jilatang has two Posyandu facilities with the number of infants and toddlers approximately 90 people. The results of interview with cadres, it is known that the cadre lacks basic knowledge about health as well as less skilled in providing counseling. Since 2009, cadres in these two posyandu have never received any refresher. The purpose of dedication is to optimize posyandu in Korong Sungai Jilatang, improve cadre skills in anthropometry measurement, improve cadre skill in motivating mother to come to posyandu and do counseling to mother of toddler. Techniques of the implementation of this devotional activity by lecture, discussion and training and followed by evaluation. The result of this devotion activity is increasing knowledge, attitude and skill of cadre in management of Posyandu. The high level of participation of program partners in the extension program, anthropometric measurement training and KMS/KIA book filling went well. This program was able to produce the outcomes expected by this community service program. Based on the results of this activity the following suggestions may be given to varied activities in posyandu to encourage mothers to bring their babies and babies to posyandu such as the availability of simple games that can be made from locally available resources. Should be changed position in the stages of activity, for example in this month activity doing registration activity, at posyandu next in the weighing section so that cadres do not experience boredom and still able to train skill.